Aggregate-bed 3D concrete printing with cement paste binder. (October 2020) - Yu, Shiwei; Du, Hongjian; Sanjayan, Jay
Abstract: 3D concrete printing (3DCP) is an emerging construction method, which has the potential to revolutionize the building industry by enabling construction automation. This paper presents a feasible concrete printing process, where cement-based filament is extruded onto aggregates bed to form layer-by-layer structures. Distinct from extrusion-based concrete printing, coarse aggregates are incorporated in the printing process and serve as the supporting material. A prototype printer has been successfully developed and aggregate content could reach about 40% in the printed concrete. Furthermore, the printed structures gained compressive strength up to 48.9 MPa and flexural strength up to 7.5 MPa at 28 days, which satisfies the general engineering requirement. Besides, an apparent mechanical anisotropy was found in printed structures and the reason of this anisotropy is the voids formed around aggregate layers and the weak interfacial transition zone located between aggregate and paste.